Ionospheric Response Observed by EISCAT During the 6–8 September 2017 Space Weather Event: Overview. Issue 9 (27th September 2018) - Yamauchi, M.; Sergienko, T.; Enell, C.‐F.; Schillings, A.; Slapak, R.; Johnsen, M. G.; Tjulin, A.; Nilsson, H.
Abstract: We present ionospheric plasma conditions observed by the EISCAT radars in Tromsø and on Svalbard, covering 68°–81° geomagnetic latitude, during 6–8 September 2017. This is a period when X2.2 and X9.3 X‐ray flares occurred, two interplanetary coronal mass ejections (ICMEs) arrived at the Earth accompanied by enhancements of MeV‐range energetic particle flux in both the solar wind (SEP event) and inner magnetosphere, and an AL < −2, 000 substorm took place. (1) Both X flares caused enhancement of ionospheric electron density for about 10 min. The X9.3 flare also increased temperatures of both electrons and ions over 69°–75° geomagnetic latitude until the X‐ray flux decreased below the level of X‐class flares. However, the temperature was not enhanced after the previous X2.2 flare in the prenoon sector. (2) At around 75° geomagnetic latitude, the prenoon ion upflow flux slightly increased the day after the X9.3 flare, which is also after the first ICME and a SEP event, while no outstanding enhancement was found at the time of these X flares. (3) The upflow velocity sometimes decreased when the interplanetary magnetic field (IMF) turned southward. (4) Before the first ICME arrival after the SEP event under weak IMF with Bz 0 nT, a substorm‐like expansion of the auroral arc signature took place without local geomagnetic signature near local midnight, while no notable change was observed after the ICME arrival. (5) AL reached <−2, 000 nT only after the arrival of the second ICME with strongly southward IMF. Causality connections between the solar/solar wind event and the ionospheric responses remain unclear. Key Points: The X9.3 flare on 6 September 2017 triggered enhancements of ionospheric electron density and temperature but not ion upflow immediately Prenoon ion upflow at 400 km altitude increased over 6–8 September 2017, but its cause can be SEP event rather than CME or X flare Substorm‐like auroral breakup was observed without notable geomagnetic signature when the interplanetary magnetic field was very weak